Development of PDA Nanoparticles for H9N2 Avian Influenza BPP-V/BP-IV Epitope Peptide Vaccines: Immunogenicity and Delivery Efficiency Improvement - Liu, Yongqing; Wang, Xiaoli; Zhou, Jiangfei; Shi, Shuaibing; Shen, Tengfei; Chen, Liangliang; Zhang, Min; Liao, Chengshui; Wang, Chen (Frontiers in Immunology, 2021)
The protection of current influenza vaccines is limited due to the viral antigenic shifts and antigenic drifts. The universal influenza vaccine is a new hotspot in vaccine research that aims to overcome these problems. Polydopamine (PDA), a versatile biomaterial, has the advantages of an excellent biocompatibility, controllable particle size, and distinctive drug loading approach in drug delivery systems. To enhance the immunogenicities and delivery efficiencies of H9N2 avian influenza virus (AIV) epitope peptide vaccines, PDA nanoparticles conjugated with the BPP-V and BP-IV epitope peptides were used to prepare the nano BPP-V and BP-IV epitope peptide vaccines, respectively. The characteristics of the newly developed epitope peptide vaccines were then evaluated, revealing particle sizes ranging from approximately 240 to 290 nm (PDI＜0.3), indicating that the synthesized nanoparticles were stable. Simultaneously, the immunoprotective effects of nano BPP-V and BP-IV epitope peptide vaccines were assessed. The nano BPP-V and BP-IV epitope vaccines, especially nano BP-IV epitope vaccine, quickly induced anti-haemagglutinin (HA) antibody production and a sustained immune response, significantly promoted humoural and cellular immune responses, reduced viral lung damage and provided effective protection against AIV viral infection. Together, these results reveal that PDA, as a delivery carrier, can improve the immunogenicities and delivery efficiencies of H9N2 AIV nano epitope vaccines, thereby providing a theoretical basis for the design and development of PDA as a carrier of new universal influenza vaccines.